Vì x;y;z >0
Nên áp dụng BĐT Cô-Si ta có: \(x+y\ge2\sqrt{xy}\Rightarrow\frac{x+y}{2}\ge\sqrt{xy}\)
\(y+z\ge2\sqrt{yz}\Rightarrow\frac{y+z}{2}\ge\sqrt{yz}\)
\(x+z\ge2\sqrt{xz}\Rightarrow\frac{x+z}{2}\ge\sqrt{xz}\)
CỘng vế theo vế ta được: \(\frac{x+y}{2}+\frac{y+z}{2}+\frac{x+z}{2}=\frac{2x+2y+2z}{2}=\frac{2\left(x+y+z\right)}{2}=x+y+z\ge\sqrt{xy}+\sqrt{yz}+\sqrt{xz}\)
P/s: sai sót xin bỏ qua cho
Áp dụng bất đẳng thức Cô-si ta có
x+y\(\ge2\sqrt{xy}\)
\(y+z\ge2\sqrt{yz}\)
\(x+z\ge2\sqrt{xz}\)
Từ đó suy ra
\(x+y+z\ge\sqrt{xy}+\sqrt{yz}+\sqrt{xz}\)